(untitled) (Journal of the College of Basic Education, 2023)
At the beginning of the year 1989 AD, the depletion of the ozone layer was considered the greatest threat to the environment, and in the meantime, the danger of desertification was forgotten because the first problem seemed more terrifying and dangerous than the second, and it had a new and unfamiliar impact.Desertification is defined as ... the decline in soil quality and, consequently, in its productive potential. This phenomenon is not new to man, as our planet has known it for thousands of years, but interest in it has begun to grow more due to the intensification of its impact on the existence of man and on his productive land.